ASSOCIATION OF MALAT1 RS3200401 GENE POLYMORPHISM WITH KIDNEY CANCER IN UKRAINIAN POPULATION - Volkogon, A. D.; Roshchupkin, A. A.; Chumachenko, Ya. D; Harbuzova, V. Yu.; Ataman, A. V. (Eastern Ukrainian Medical Journal, 2019)
Introduction. As it is known, only 2 % of the human genome encodes proteins, while the greater part of the genome corresponds to non-coding sequences. In the recent years among a large variety of non-coding sequences special attention of researchers was drawn to long non-coding RNA MALAT1. This sequence first was detected in 2003 in non-small cell lung cancer cells. Today the results of numerous experiments revealed that MALAT1 is one of the major genes involved in various types of cancer, including kidney cancer.Purpose. To study the association between MALAT1 rs3200401 polymorphism and kidney cancer development in Ukrainian population.Materials and methods. 101 patients with kidney cancer (renal cell carcinoma) was enrolled into the study. The final diagnosis was based on anamnesis data, clinical, biochemical and instrumental examinations according to the recommendations of European Association of Urology. All participants were treated in the hospital of Sumy Regional Oncology Center. The control group included 100 healthy individuals without personal cancer history. The study of MALAT1 rs3200401 SNP was perfprmed by Real-time PCR using 7500 Fast Real-time PCR System (Applied Biosystems, Foster City, USA) and Taq-Man Assays (TaqMan®SNP Assay C_3246069_10). Statistical analyses were performed using Statistical Package for Social Science software (SPSS, version 17.0, Chicago, IL, USA) and online resource “SNIPKA”.Results. The distribution of CC-homozygotes, CT-heterozygotes and TT-homozygotes in patients with kidney cancer was 71 (70.3%), 29 (28.7 %) and 1 (0.99 %), respectively. In the control group, distribution of genotypes was 59 (59.0 %), 32 (32.0 %) and 9 (9.0 %), respectively. The significant difference in genotypes distribution between kidney cancer patients and the control group was found (P = 0.022). Genotypic analysis has shown that T-minor allele carriers had less risk of kidney cancer development compared to patients with CC-genotype (P = 0.031, OR = 0.101, 95 % CI = 0.013–0.814).Conclusion. There is statistically significant link between MALAT1 rs3200401 polymorphism and kidney cancer development in Ukrainian population. Individuals with minor T-allele (TT- and CT-genotypes) have less risk of renal cell carcinoma development compared to major homozygotes (CC).